Paper towns - Green, John (Speak, 2012)
One month before graduating from his Central Florida high school, Quentin "Q" Jacobsen basks in the predictable boringness of his life until the beautiful and exciting Margo Roth Spiegelman, Q's neighbor and classmate, takes him on a midnight adventure and then mysteriously disappears.